Health Belief Model Predictors of Behavioral Intention to Use Emergency Healthcare Services among Diabetic Patients: A Cross-Sectional Study - Altherwi, Tawfeeq (International Journal of Statistics in Medical Research, 2026)
Background: Emergency healthcare services are critical for diabetic patients experiencing acute complications; however, timely utilization remains inconsistent. In Saudi Arabia, limited evidence exists regarding the cognitive factors influencing emergency care-seeking intentions. Aim: To examine Health Belief Model (HBM) predictors of behavioral intention to use emergency healthcare services among diabetic patients in the Jazan region. Methods: A cross-sectional survey of 250 diabetic patients was conducted using validated Arabic questionnaires assessing six HBM constructs. Hierarchical binary logistic regression evaluated HBM constructs (Model 1) and additional demographic/clinical variables (Model 2). Results: Most participants (64.4%) demonstrated low intention to use emergency services. HBM constructs significantly predicted behavioral intention (χ²=16.916, p=0.010). Significant predictors were Cues to Action (OR=1.174), Perceived Susceptibility (OR=1.149), Self-Efficacy (OR=1.126), and Perceived Barriers (OR=0.880). Adding demographic variables did not significantly improve model fit (p=0.475). Conclusion: Health beliefs, rather than demographic characteristics, primarily determine emergency service utilization intentions among diabetic patients. Interventions should target symptom recognition, perceived vulnerability, self-efficacy, and access barriers to enhance timely emergency care-seeking.